Romans 10:5–13 revisited - Oliver, Willem (HTS teologiese studies, 2015)
The aim of this article is to investigate Romans 10:5–13 and specifically the impact of the chiasm (chiasmus) in Romans 10:9–10 on this sub-pericope. In the chiasm Paul makes the following statement(s):A If you confess with your mouth Jesus as LordB and believe in your heart that God raised him from the dead,C you will be saved.B For with the heart a person believes, resulting in righteousness,A and with the mouth/he confesses, resulting in salvation.What gives the chiasm existential value here is the fact that this is the only passage in which Paul uses confess with your mouth as a condition for salvation. The sub-pericope will be discussed against the background of the introduction to the letter (Rm 1:16–17) as well as Romans 3:21–31.